A Proposal for the Interpretation of Serum IGF-I Concentration as Part of Laboratory Screening in Children with Growth Failure - Jan M. Wit; Martin Bidlingmaier; Christiaan de Bruin; Wilma Oostdijk (Galenos Yayincilik, 2020)
The serum insulin-like growth factor-I (IGF-I) concentration is commonly used as a screening tool for growth hormone deficiency (GHD), but there is no consensus on the cut-off limit of IGF-I standard deviation score (SDS) to perform GH stimulation tests for confirmation or exclusion of GHD. We argue that the cut-off limit is dependent on the clinical pre-test likelihood of GHD and propose a diagnostic strategy in which the cut-off limit varies between zero to -2 SDS.